2019
DOI: 10.1002/arp.1745
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral remote sensing for post‐dictive analysis of archaeological remains. A case study from Bronte (Sicily)

Abstract: In recent years, the use of remote sensing in archeology has rapidly grown, having being proven particularly useful for landscape archaeology investigations. The quality of results obtained through remote sensing mainly depends on the number of bands that can be exploited, the spatial and spectral resolution of imagery and the methodology used. In this work, adopting a post‐dictive approach, multispectral remote sensing data from World‐View 2 (WV‐2) were used in order to detect archaeological features in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…GIS technology represents a valid tool to support archaeological activities for both postdictive and predictive analysis, as demonstrated by numerous works in the literature Gennaro et al,2018;2019a;2019b;Mangiameli et al, 2020). In particular, in the archaeological field, the integrated use of GIS technology and data acquired by satellite sensors represents an effective approach in difficult territorial contexts, such as volcanic areas, areas of variable geomorphology, little outcropping features, etc.…”
Section: The Gis Technologymentioning
confidence: 99%
“…According to the optimal index expression, it can be seen that the smaller the correlation coefficient, the greater the optimal index value, and the amount of information increases as the correlation coefficient decreases, so the optimal index and the corresponding combined image information amount are positively correlated (Gennaro et al, 2019).…”
Section: Uav Multispectral Remote Sensing Image and Its Preprocessingmentioning
confidence: 99%